First person - Dimitrije Stanković (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Dimitrije Stanković is first author on 'A Drosophila model to study retinitis pigmentosa pathology associated with mutations in the core splicing factor Prp8', published in DMM. Dimitrije is a PhD student in the lab of Mirka Uhlirova at CECAD Research Center in Cologne, Germany, investigating the functional consequences of aberrant pre-mRNA splicing in the context of regulation of gene expression, activation of stress signaling pathways and DNA damage.